Revealing the Contribution of Phytochemicals in Syzygium cumini as Diabetics: A Systematic Review - Endra Pujiastuti; Agung Endro Nugroho; Khoirun Nisa; Triana Hertiani (Indonesian Journal of Pharmacy, 2023)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by increased blood glucose and abnormal carbohydrates, fats and proteins metabolism. Syzygium cumini (L.) Skeels (Myrtaceae) are widely used in anti-diabetic remedies and at the same time, rich in polyphenols. This study aims to provide a comprehensive review on the role of phytochemicals in Syzygium cumini to contribute in its anti-diabetic. The review covers related articles to antidiabetic AND Syzygium cumini AND phytochemicals OR bioactive which were published from 2012 to 2023. A systematic search was conducted by using databases Pubmed, Science Direct, Scopus, and Google The inclusion criteria include articles written in English as experimental research or clinical trials, randomized studies, and should contains phytochemical content profiling The exclusion criteria were other type of reports and or irrelevant to aforementioned topic. This review was written according to the reporting items guidelines for systematic payments and Meta-analysis (PRISMA), and SYRCLE's risk of bias (RoB) tool. By the systematic compensation used, 13 articles that meet the requirements were obtained and were further thoroughly reviewed. Seeds, leaves and bark of plant parts were reported to non-toxic in acute experiments on mice or rat. S. cumini contains flavonol glycosides, especially myricetin, myricitrin, quercetin, and kaempferol; phenolics, such as ellagic acid, tannins, gallic acid; alkaloids and saponins. These compounds contribution to the overall anti-diabetic activity were discussed, i.e increase of insulin sensitivity, secretion and usage of glucose in tissues; reducing insulin resistance, oxidative stress, gluconeogenesisand absorption of carbohydrates and sucrose. The seeds and leaves of S. cumini exhibit high potential to be developed as herbal products for anti-diabetics. This review finds a gap in research to support the development of the herbs as herbal products for anti-diabetics, in form of established preclinical and clinical trials and a reliable analytical methods for the phytochemical profiling.